2011
DOI: 10.1038/sc.2011.91
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone reduced methylprednisolone-induced muscle atrophy in spinal cord-injured rats

Abstract: Study design: Male rats with complete transections of the spinal cord were administered vehicle or methylprednisolone (MP) for 24 h, with or without infusion, for 7 days, of testosterone at either a replacement or low pharmacological doses. Muscles were collected at 7 days after SCI. Objective: The objective of this study is to determine, in a rat model of complete spinal cord transection, whether testosterone reduces muscle atrophy or upregulates muscle atrophy-linked genes, induced by 24 h of MP administrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 33 publications
(64 reference statements)
0
13
0
Order By: Relevance
“…Indeed, Byers et al also reported that testosterone profoundly improved muscle fCSA in the vastus lateralis of young rodents after moderate contusion SCI, a model that exhibits spontaneous voluntary locomotor recovery after injury [ 21 ]. In comparison, Wu et al reported that testosterone treatment alone did not ameliorate muscle loss in several plantar flexor muscles in young rodents after spinal cord transection, a model that exhibits negligible sublesional weight bearing after injury, but that testosterone completely prevented the supplemental muscle loss induced by methylprednisolone [ 23 , 24 ]. Although, at least one group has reported preservation of plantar flexor and vastus lateralis muscle CSA in rodents after spinal cord transection [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, Byers et al also reported that testosterone profoundly improved muscle fCSA in the vastus lateralis of young rodents after moderate contusion SCI, a model that exhibits spontaneous voluntary locomotor recovery after injury [ 21 ]. In comparison, Wu et al reported that testosterone treatment alone did not ameliorate muscle loss in several plantar flexor muscles in young rodents after spinal cord transection, a model that exhibits negligible sublesional weight bearing after injury, but that testosterone completely prevented the supplemental muscle loss induced by methylprednisolone [ 23 , 24 ]. Although, at least one group has reported preservation of plantar flexor and vastus lateralis muscle CSA in rodents after spinal cord transection [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Testosterone also influences musculoskeletal integrity after SCI, as evidenced by (1) the high prevalence of low testosterone in men [ 14 ] and rodents after SCI [ 2 , 15 , 16 ], (2) the ability of androgens to prevent SCI-induced bone loss in young [ 16 , 17 ] and skeletally-mature animals [ 2 , 15 ], and (3) the ability of testosterone to improve lean mass [ 18 , 19 ] and muscle cross-sectional area in men with motor-complete SCI [ 20 ]. However, studies evaluating the myotrophic effects of androgens in rodent muscle after SCI have produced conflicting results, with some reporting that testosterone partially preserves hindlimb muscle mass [ 16 , 21 , 22 ] and others reporting no prevention of muscle atrophy [ 23 , 24 ]. Indeed, we have observed that testosterone-enanthate (TE) completely preserved mass of the sublesional non-weight bearing levator ani/bulbocavernosus (LABC) muscle complex after SCI [ 15 ], while producing a much less robust effect in the soleus [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…(10,11) Loss of testosterone, as a consequence of aging or castration surgery, leads to muscle atrophy and muscle weakness. (10,11) Loss of testosterone, as a consequence of aging or castration surgery, leads to muscle atrophy and muscle weakness.…”
Section: Introductionmentioning
confidence: 99%
“…Testosterone is an anabolic hormone produced by the Leydig cells of the testes and plays a major role in the regulation of muscle mass in males. (10,11) Loss of testosterone, as a consequence of aging or castration surgery, leads to muscle atrophy and muscle weakness. (12,13) Testosterone modulates muscle anabolism not only via signaling networks that are directly orchestrated by itself, but also indirectly via other hormones such as follicle-stimulating hormone, luteinizing hormone, and growth hormone (14,15) due to widely expressed androgen receptors in endocrine organs, including bone.…”
Section: Introductionmentioning
confidence: 99%
“…In response to spinal cord injury, MP mediates antioxidative, antiinflammatory, and immunosuppressive effects; stabilizes cell and lysosomal membranes; reduces medullospinal tissue deficiency at the injured site; improves blood flow to the injured spinal cord segment; reduces edema; increases the activity of Na+/K+-dependent ATP enzyme; increases the resting potentials and excitabilities of spinal cord motor fibers; and promotes the generation and conduction of spinal cord impulses 8 . In this study, we observed the impact of MP on medullospinal edema in rats with ASCI, and investigated the Kir4.1-and AQP4-related mechanisms of MPmediated suppression of medullospinal edema in rats with ASCI.…”
mentioning
confidence: 99%